2012
DOI: 10.1097/ss.0b013e3182408f1e
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Tillage and Fertilization Impact on Soil Aggregation and Carbon Pools in the Indian Himalayas Under an Irrigated Rice-Wheat Rotation

Abstract: Soil conservation and carbon sequestration are critical issues in the Indian Himalayas. This study, conducted from 2005 through 2009 on a sandy clay loam soil near Almora, India, with two tillage (conventional tillage [CT] and zero tillage [ZT]) and five fertilization management practices (100% NPK [F1], 50% NPK + 10 Mg farmyard manure [FYM] ha j1 [F2], 50% NPK + 10 Mg poultry manure [PM] ha j1 applied on equivalent N basis of 10 Mg FYM ha j1 [F3], 100% NPK + 10 Mg FYM ha j1 [F4], and 100% NPK + 10 Mg PM ha j1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 42 publications
(65 reference statements)
1
36
0
Order By: Relevance
“…The interaction among soil aggregate size distribution, SOC contents and aggregate stability indices is still not well understood (Blanco-Canqui and Lal, 2004). Meanwhile, little information is available about whether soil aggregate stability is positively or negatively correlated with soil C (Six et al, 2002;Bhattacharyya et al, 2012). Based on recent literature, it is perceived that less studies have investigated the interactive effects of tillage and straw returning in rice-rape rotation system regarding SOC and water stable aggregation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction among soil aggregate size distribution, SOC contents and aggregate stability indices is still not well understood (Blanco-Canqui and Lal, 2004). Meanwhile, little information is available about whether soil aggregate stability is positively or negatively correlated with soil C (Six et al, 2002;Bhattacharyya et al, 2012). Based on recent literature, it is perceived that less studies have investigated the interactive effects of tillage and straw returning in rice-rape rotation system regarding SOC and water stable aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…The soil management practices are considered essential to conserve soil quality (Kahlon et al, 2013), and can greatly affect the composition and stability of SOC through plough layer (Stone and Schlegel, 2010;Bhattacharyya et al, 2012;Ghosh et al, 2016). Conventional tillage (CT) could reduce the SOC content and accelerate SOC oxidation rate, probably due to the disturbance of soil aggregates and the increase of the soil aeration (Gathala et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Pandey et al, (2014) revealed that no-tillage before sowing of rice and wheat could increase SOC by 0.59 Mg C ha -1 yr -1 . The rate of SOC sequestration due to reduced-or no-tillage management in rice-based systems in South Asia varied from 0-to 2114 kg ha -1 yr -1 (Bhattacharyya et al, 2012a).…”
Section: Soil Organic Carbon Distributionmentioning
confidence: 99%
“…The VS reduces runoff and soil loss by deposition of sediments carried by runoff water behind the strips to form vegetative bund over the years [20,24], whereas weed mulch reduces rainfall's erosion potential by preventing breaking down of large water stable aggregates that reduces soil erosion [24]. Reduction of runoff and soil through bio-resources (FYM, VC and PM) recycling is expected as carbon input from organic sources helps in formation of more water stable macro-aggregates [6]. As independent components of CA reduce runoff and soil loss, therefore, interaction effect of the components obviously reduces runoff and soil loss by higher quantity.…”
Section: Runoff and Soil Lossmentioning
confidence: 99%
“…When vegetation strips integrate with reduced tillage, nutrient management (bio-resources like FYM, vermi-compost and poultry manure) and weed management, it can lead to a sustainable production system in Indian sub-Himalayas where *82 % of the population lives in rural areas and is chiefly dependent upon crop farming [5]. Minimum tillage is recommended for soils of the Indian Himalayan region due to reduced cost of cultivation, more retention of soil water and physical protection of soil organic carbon (SOC) in the aggregates [6]. Bio-resource in situ (weed live mulch) and ex situ (FYM, vermi-compost, poultry manure) recycling not only fulfils nutrient requirement of a crop cycle but also increases soil water storage.…”
Section: Introductionmentioning
confidence: 99%